Ecosystem management and the conservation of caribou habitat in British Columbia - Seip, Dale R. (Rangifer, 1998)
Woodland caribou (Rangifer tarandus caribou) in British Columbia inhabit a wide variety of forest ecosystems. Numerous research projects have provided information that has been used to develop caribou habitat management recommendations for different areas. Recently, the province has implemented guidelines to protect biodiversity that are based on an ecosystem management strategy of mimicking natural forest conditions. There is a great deal of similarity between caribou management recommendations and biodiversity recommendations within different forest types. In mountain caribou habitat, both approaches recommend maintaining a landscape dominated by old and mature forests, uneven-aged management, small cutblocks, and maintaining mature forest connectivity. In northern caribou habitat, both approaches recommend maintaining some older stands on the landscape (but less than for mountain caribou), even-aged management, and a mosaic of large harvest units and leave areas. The ecosystem management recommendations provide a useful foundation for caribou habitat conservation. More detailed information on caribou and other management objectives can then be used to fine-tune those recommendations.